Оптимизация расчета конструктивных параметров элементов решетчатых противокумулятивных экранов - Мазур, Игорь Витальевич; Грабовский, Андрей Владимирович; Ткачук, Николай Анатольевич; Мормило, Яков Михайлович (Национальный технический университет "Харьковский политехнический институт", 2016)
Разработана методика оптимизации основных конструктивных параметров элементов решетчатых противокумулятивных экранов для защиты от кумулятивного боеприпаса, в частности от гранат ручного противотанкового гранатомета. На основе этой методики, исходя из требований противодействия конкретному типу боеприпаса, возможен подбор оптимальной, по массогабаритным показателям и с максимально допустимой вероятностью срабатывания, конструкции противокумулятивного решетчатого экрана.

The article analyzes the existing cumulative ammunition in different countries, as well as show-characterized tics of various anti-tank grenade. The analysis of the means of protection against chemical weapons, are examples of the use anti-cumulative screens. A method for optimizing the basic design data elements anti-cumulative lattice screens to protect against cumulative ammunition, especially grenades rocket-propelled grenade. The analysis of the calculated data shows that the use of the proposed method provides a rationale for the choice of the design parameters of the elements of lattice screens. This technique allows you to automate the calculation of parameters of elements-cops lattice screens to protect against the alleged type of munition and optimization of lattice screens for specific tasks. Comparison of the calculated performance data grid displays the characteristics of existing models shows their convergence.
Optimization and calculation of design parameters lattice elements anti-cumulative shields
Keywords: бронетанковая техника; легкобронированная техника; кумулятивные боеприпасы; РЭ; боевые бронированные машины; горизонтальный элемент; armored vehicles; light armored vehicles; passive protection